2019
DOI: 10.1093/neuros/nyy632
|View full text |Cite
|
Sign up to set email alerts
|

Limited Dorsal Myeloschisis: Reconsideration of its Embryological Origin

Abstract: BACKGROUND Limited dorsal myeloschisis (LDM) is postulated to be a result of incomplete dysjunction in primary neurulation. However, clinical experience of LDM located below the first-second sacral (S1-S2) vertebral level, which is formed from secondary neurulation (S2-coccyx), suggested that LDM may not be entirely explained as an error of primary neurulation. OBJECTIVE To elucidate the location and characteristics of LDM to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
1
14
0
5
Order By: Relevance
“…In the present case, the morphology of the association between RMC and CDS differed from that of the typical association between LDM and CDS, and the C-LS of the RMC was extended to become an extradural stalk with CDS elements. In a study by Kim et al [22], 11 out of 28 LDMs were located below the S1–2 vertebral level, suggesting that it had been caused by errors in secondary neurulation. In the present case, the RMC may have terminated in an LDM stalk located below the bifid S1 level, with CDS elements during secondary neurulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the morphology of the association between RMC and CDS differed from that of the typical association between LDM and CDS, and the C-LS of the RMC was extended to become an extradural stalk with CDS elements. In a study by Kim et al [22], 11 out of 28 LDMs were located below the S1–2 vertebral level, suggesting that it had been caused by errors in secondary neurulation. In the present case, the RMC may have terminated in an LDM stalk located below the bifid S1 level, with CDS elements during secondary neurulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, my team reported that LDM may be found in the area of secondary neurulation (Fig. 2) 11) . The continuation of the caudal cell mass with the surface-located primitive streak in the early phase of secondary neurulation gives the chance for non-disjunction to occur.…”
Section: Limited Dorsal Myeloschisis (Ldm)mentioning
confidence: 98%
“…Recently, through the methods mentioned above, our team reported that LDM may be found in the area of secondary neural tube [ 27 ] ( Fig. 10 ).…”
Section: Focal Limited Dorsal Neuro-cutaneous Nondisjunctionmentioning
confidence: 99%